Identifying aggregate shocks with micro-level heterogeneity: Financial shocks and investment fluctuation - Xing Guo (Bank of Canada, 2020)
This paper identifies the aggregate financial shocks and quantifies their effects on business investment based on an estimated DSGE model with firm-level heterogeneity. On average, financial shocks contribute only 1.1% of the variation in U.S. public firms' aggregate investment. The negligible aggregate relevance of financial shocks mainly results from the interaction between firm-level heterogeneity and general equilibrium effects. Following a contractionary financial shock, financially constrained firms are directly forced to cut investment, which dampens the aggregate investment demand and lowers the capital good price. The lower capital good price motivates the financially unconstrained firms to invest more, which largely cancels out the financial shock's direct effect in aggregation. If the firm-level heterogeneity is removed, the implied relevance of financial shocks to aggregate investment will be 50 times larger. This sharp difference indicates that representative firm models could overstate the relevance of financial shocks in driving the business cycle fluctuation and highlights the importance of micro-level heterogeneity in identifying the aggregate shocks.
Keywords: E12; E22; G31; G32; 330; Business fluctuation and cycles; Firm dynamics